Analyzing Geology textbooks for secondary school curricula in Greece and Spain: Educational use of geological heritage - Meléndez, G.; Fermeli, G.; Koutsouveli, An. (Bulletin of the Geological Society of Greece, 2007)
The teaching of geology as a separate discipline in secondary school curricula has been progressively reduced during the last 20 years in European countries. In the case of Greece and Spain, National Education laws have set geology as a supplementary matter of biology, geography and environmental sciences. However, geology and Earth sciences are not subsidiary items of these "natural science" disciplines. This secondary role assigned to geology is creating serious concern among geologist community due to the substantial drop of geology contents in Secondary school curricula, which will presumably produce a consequent drop of geology students in universities and the lack of geologists in the society. A proposal is made for using geological heritage as an educational tool and incorporating it to textbooks. This means using relevant points of geological and palaeontological heritage, as well as erosional features and fossil sites and relevant remains to illustrate natural processes and the History of Earth. This might provide a valuable instrument to create social and political concern for both Earth sciences and geological heritage, as well as to raise interest and enthusiasm in Secondary school students for the knowledge of Earth.